Colonisation with extended spectrum beta-lactamase producing and carbapenem-resistant enterobacterales in children admitted to a paediatric referral hospital in South Africa - Ogunbosi, Babatunde Oluwatosin (Department of Paediatrics and Child Health, 2021)
Introduction: There are few studies describing colonisation with extended spectrum beta-lactamase-producing Enterobacterales (ESBL-PE) and carbapenem-resistant Enterobacterales (CRE) among children in subSaharan Africa. Colonisation often precedes infection and multi-drug-resistant Enterobacterales are important causes of invasive infection. Methods: In this prospective cross-sectional study, conducted between April and June 2017, 200 children in a tertiary academic hospital were screened by rectal swab for EBSL-PE and CRE. The resistance-conferring genes were identified using polymerase chain reaction technology. Risk factors for colonisation were also evaluated. Results: Overall, 48% (96/200) of the children were colonised with at least one ESBL-PE, 8 of these with 2 ESBLPE, and one with a CRE (0.5%, 1/200). Common colonising ESBL-PE were Klebsiella pneumoniae (62.5%, 65/104) and Escherichia coli (34.6%, 36/104). The most frequent ESBL-conferring gene was blaCTX-M in 95% (76/80) of the isolates. No resistance- conferring gene was identified in the CRE isolate (Enterobacter cloacae). Most of the Klebsiella pneumoniae isolates were susceptible to piperacillin/tazobactam (86.2%) and amikacin (63.9%). Similarly, 94.4% and 97.2% of the Escherichia coli isolates were susceptible to piperacillin/tazobactam and amikacin, respectively. Hospitalisation for more than 7 days before study enrolment was associated with ESBL-PE colonisation. Conclusion: Approximately half of hospitalised children in this study were colonised with ESBL-PE. This highlights the need for improved infection prevention and control practices to limit the dissemination of these microorganisms.